Calcitriol-mediated reduction in IFN-γ output in T cell large granular lymphocytic leukemia requires vitamin D receptor upregulation. Issue 177 (March 2018) - Kulling, Paige M.; Olson, Kristine C.; Olson, Thomas L.; Hamele, Cait E.; Carter, Kathryn N.; Feith, David J.; Loughran, Thomas P.
Highlights: IFN-γ levels and p-STAT1 are reduced by calcitriol within 4 h in TL-1 cell line. IFN-γ is transcriptionally suppressed by calcitriol and requires VDR upregulation. Reduction in p-STAT1 by calcitriol does not require VDR upregulation. In the absence of calcitriol, VDR levels correlate with IFN-γ production. Calcitriol reduces IFN-γ to a similar amount regardless of basal VDR levels. Abstract: Constitutively activated STAT1 and elevated IFN-γ are both characteristic of T cell large granular lymphocytic leukemia (T-LGLL), a rare incurable leukemia with clonal expansion of cytotoxic T cells due to defective apoptosis. Interferon gamma (IFN-γ) is an inflammatory cytokine that correlates with worse progression and symptomology in multiple autoimmune diseases and cancers. In canonical IFN-γ-STAT1 signaling, IFN-γ activates STAT1, a transcription factor, via phosphorylation of tyrosine residue 701 (p-STAT1). p-STAT1 then promotes transcription of IFN-γ, creating a positive feedback loop. We previously found that calcitriol treatment of the TL-1 cell line, a model of T-LGLL, significantly decreased IFN-γ secretion and p-STAT1 while increasing the vitamin D receptor (VDR) protein. Here we further explore these observations. Using TL-1 cells, IFN-γ decreased starting at 4 h following calcitriol treatment, with a reduction in the intracellular and secreted protein levels as well as the mRNA content. A similar reduction in IFN-γ transcript levels was observed in primary T-LGLL patient peripheral blood mononuclear cells (PBMCs). p-STAT1 inhibition followed a similar temporal pattern and VDR upregulation inversely correlated with IFN-γ levels. Using EB1089 and 25(OH)D3, which have high or low affinity for VDR, respectively, we found that the decrease in IFN-γ correlated with the ability of EB1089, but not 25(OH)D3, to upregulate VDR. However, both compounds inhibited p-STAT1; thus the reduction of p-STAT1 is not solely responsible for IFN-γ inhibition. Conversely, cells treated with VDR siRNA exhibited decreased basal IFN-γ production upon VDR knockdown in a dose-dependent manner. Calcitriol treatment upregulated VDR and decreased IFN-γ regardless of initial VDR knockdown efficiency, strengthening the connection between VDR upregulation and IFN-γ reduction. Our findings suggest multiple opportunities to further explore the clinical relevance of the vitamin D pathway and the potential role for vitamin D supplementation in T-LGLL.